Revitalisasi Komunikasi Sosial di Era Modern - Khoirunnisak, Anis; Febriana, Arofah Nur; Mansur, Mansur; Hermawati, Anggy; Sani, Muhamad Usman (Journal of Democratia; Vol 3 No 1 (2025): Jurnal Democratia : Pendidikan Pancasila dan Kewarganegaraan, Moral, Karakter, dan Hukum, 2024)
The aim of this research is to describe the revitalization of social communication in the modern era. Describe social communication methods before the Covid-19 pandemic, understand the impact of the modern era on social communication and various aspects of people's lives, and describe social communication during the modern era. This research uses qualitative research methods and a descriptive approach. Qualitative research method with a descriptive approach, namely a series of activities to obtain data that is as it is without being in certain conditions, the results of which emphasize meaning. The data source used in this research comes from a literature review. The time for this research is November to December 202 4 The results of this research explain how the revitalization of social communication is the impact of the modern era as an effort so that social communication can run effectively even though the modern era is still attacking Indonesia today. Based on the results of this research, it can be concluded that the modern era has changed social communication patterns in society. Therefore, there needs to be a strategy that can be implemented so that social communication can continue to run effectively, namely continuing to preserve culture and foster unity and increase the sense of brotherhood or solidarity among the community.